Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms 2009
DOI: 10.1137/1.9781611973068.38
|View full text |Cite
|
Sign up to set email alerts
|

High rate fingerprinting codes and the fingerprinting capacity

Abstract: Including a unique code in each copy of a distributed document is an effective way of fighting intellectual piracy. Codes designed for this purpose that are secure against collusion attacks are called fingerprinting codes.In this paper we consider fingerprinting with the marking assumption and design codes that achieve much higher rates than previous constructions. We conjecture that these codes attain the maximum possible rate (the fingerprinting capacity) for any fixed number of pirates. We prove new upper b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(129 citation statements)
references
References 6 publications
(36 reference statements)
3
124
0
Order By: Relevance
“…Under the arbitrary digit model they can put arbitrary symbols in detectable positions, while the general digit model additionally allows erasures at detectable positions. 1 …”
Section: Collusion Attacks Against Forensic Watermarkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the arbitrary digit model they can put arbitrary symbols in detectable positions, while the general digit model additionally allows erasures at detectable positions. 1 …”
Section: Collusion Attacks Against Forensic Watermarkingmentioning
confidence: 99%
“…When this is the case, the statistical analysis of the code's performance can be drastically simplified; the performance is almost completely determined by a single parameter, namely the average scoreμ of the coalition. The Gaussian assumption is motivated by the Central Limit Theorem (CLT): A user accusation consists of a sum of per-segment contributions, which are independent and identically distributed 1 The proportionality m ∝ c 2 0 was already known in the context of spread-spectrum watermarking. Kilian et al [9] showed that, if the watermarks have a component-wise normal distribution, then Ω( p m/ln n) differently marked copies are required to successfully erase any mark with non-negligible probability.…”
Section: Exact Computation Of the False Positive Error Probabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Kilian et al [13] showed that, if the watermarks have a component-wise normal distribution, then Ω( √ m/ln n) differently marked copies are required to successfully erase any mark with non-negligible probability. 2 Not to be confused with the total false positive probability (which we denote as η). The relation is η…”
Section: Tardos Codesmentioning
confidence: 99%
“…In contrast, one can also use a 'joint decoder' which considers sets of users. Amiri and Tardos [2] have given a capacity-achieving joint decoder construction for the binary code. (Capacity refers to the informationtheoretic treatment [11,16,22] of the colluder attack as a communication channel.)…”
Section: Tardos Codesmentioning
confidence: 99%